MOUSETOWN : 30+ kids crafts made from recycled and everyday materials - Levine, Jodi; McCartney, Margaret (New York : Union Square Kids, 2024)
"An arts and crafts book with a story about Mouse and his day in Mousetown with over thirty crafts to make"-- Provided by publisher
Keywords: Miniature craft -- Juvenile literature; Diorama